Development of Algorithm for QoS Model in Cloud Computing - Alfadli, Mohammed Abdullah; Noordin, Mohamad Fauzan; Billah, Md. Masum (Medwell Publications, 2021)
In this study, we will develop an algorithm for the QoS Model. It starts with studying four algorithms and explain the experimental setup for them. Then, we simulate them, get the results and discuss results for all algorithms. After that, we will develop our new algorithm for the QoS Model. Then, we simulate the new enhanced algorithm and compare to other algorithms.